Effect of Shielding Gas on Microstructures and Mechanical Properties of TC4 Titanium Alloy Ultranarrow Gap Welded Joint by Laser Welding with Filler Wire. (2nd August 2021) - Fang, Naiwen; Guo, Erjun; Xu, Kai; Huang, Ruisheng; Ma, Yiming; Zeng, Caiyou; Yang, Yicheng; Xie, Jilin; Cao, Hao
Abstract : A 20 mm thick TC4 titanium alloy plate was welded by ultranarrow gap laser welding with filler wire with Ar and He as shielding gas, respectively. A characterization analysis of the microstructures and mechanical properties of the welded joint was conducted with OM, SEM, XRD, and EBSD and through the microhardness test and tensile test. The results showed that HAZ of the welded joint formed with Ar as shielding gas was much wider than that with He, and weld microstructure composition with the two shielding gases was basically consistent; phase boundary of the weld metal obtained with Ar was clearer, with a larger misorientation between the laths; α ′ martensite lath in weld metal prepared with He showed obvious preferred orientation distribution, and α ′ martensite microstructure was much finer; the misorientation of α ′ phase grain boundary of weld microstructure prepared with Ar was slightly less distributed in high angle grain boundary than that with He; tensile property of the welded joint prepared with He was better than that with Ar; the hardness of each zone of welded joint prepared with He was less fluctuated and the hardness value measured was slightly higher than that with Ar.